The French Army 1750-1820 - Blaufarb, Rafe (Manchester University Press, 2017)
This book examines the transformation of the French military profession during the momentous period that saw the death of royal absolutism, the rise and fall of successive revolutionary regimes, the consolidation of Napoleonic rule and the restoration of the Bourbon monarchy after the Empire’s final collapse. Crossing traditional chronological boundaries, it brings together periods in French history that are usually treated separately and challenges established views of change and continuity during the Age of Revolution. Based on a wealth of archival sources, this book is as much a social history of ideas like equality, talent, and merit as a military history.